Innovation output and state ownership: Empirical evidence from China's listed firms - Kou Kou; Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2017)
China has experienced a surge in innovation output in which state-owned enterprises (SOE) play an essential role. Using panel data of Chinese listed firms, this paper examines the influence of the state ownership on innovation output at the firm level. Controlling for size, we analyse the effects of central and local government control on the number of firms' patent applications in different time periods. Doing so, standard assumptions on state ownership's inhibiting character are confirmed. However, we then qualify these finding by running separate models for different regions and sectors find that the impact of state-control on innovation performance depends on a number of conditions. More precisely, state control of firms has a negative impact on innovation output in particular in China's Northeast region and in mid-tech sectors whereas under other circumstances it does either not matter or can even exert a positive influence.
urn:nbn:de:0011-n-4357769
Keywords: 330